LINGUISTIC MARKERS OF ETHNIC IDENTITY: ANALYZING THE USE OF UZBEK DIALECTS AND CODE-SWITCHING IN EVERYDAY SPEECH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores how linguistic variations, particularly dialects and code-switching practices among Uzbek-speaking communities, serve as markers of ethnic and cultural identity. By examining everyday speech patterns, the research highlights the role of language in expressing group affiliations and individual identities within diverse social contexts.*